The most important of the UAE, the Kurdish tribes and the policy of Daoud Pasha, its direction (the Babanian family) is a model (Journal of the College of Basic Education, 2025)
The most important thing that came from the research is the knowledge of the most important emirates and other Kurdish tribes, consisting of northern Iraq, as these clans enjoyed great influence and power that made them an autonomous authority and not subject to the control of the governors of Baghdad. The research also indicated the knowledge of Kurdish origins and the nature of the areas they inhabit, which had a large part of their steadfast survival under many military conditions. The research also touched on identifying the largest ruling emirates in Kurdistan, including the Emirate of Bahdinaniya, which is located in Al-Hammadiya in the far north of Iraq, which began its rule in 1329 and continued until the reign of Sultan Salim in 1514 AD. The Suranian Emirate, which was founded in the twelfth century AD, which became one of the strongest emirates during the reign of Prince Mohammed Al-Rawandozi, who is one of the most famous ruwand princes, and Prince Mohammed was distinguished by steverness and strength of personality. Muhammad Pasha was able to expand the scope of his rule and unify it under his leadership and build a great strength that can withstand Ottoman and Iranian ambitions.As for the most important strong Kurdish clans and nerves, it is the Al-Jaf clan, which is located in Sulaymaniyah on the borders of Iran, Iraq, the Shader clan, Al-Balbs, Al-Dizh Bei, Al-Hamwand, and the Yazi tribesm all live in the northern regions of Iraq. These clans realized the importance of their geographical location, which had an important role in strengthening their military strength. The Kurds of this region took cared about their interests first, as they used to use the Iranian forces, as they did not face danger from the governors of Baghdad once and again, using the governors of Baghdad, as they did not face the danger of Iranian forces. The northern region is also considered a permanent conflict and has constituted a heavy burden on the governors of Baghdad due Control of it, several families have been established in this region, the most important of which is the Papan family, which played a major role in the course of historical events in this region. As for the Pabanic family, whose origins go back to Lahijan, it is an Iranian city located in Ghilan province. This family arose in the late fifteenth century or early sixteenth century in the east of the Emirate of Soran, and included some tribes, the most important of which was Mokri. This family was also able to expand its influence until it reached the Emirate of Ardlan and then to Kirkuk, and at the beginning of the eighth century, this family became one of the strongest Kurdish families. These families were founded by a man named (Fakih Ahmed) in the district of Shadlar, and began to expand during the reign of Fakih Ahmed and his son Khan Bodak by seizing some areas, including Mahat, Shahrbazar and the neighboring districts. In addition to the joining of some neighboring clans, including the big Balbas clan and some of its inhabiting branches in Iran, Khan Boudaq died in 1665, thus ending the first era of the family.In (1969-1699), Baba Suleiman, the son of Khan Boudaq, who is the true founder of the Bababan family, took over.His rule was characterized by the political character of the emirate after it was feudal or tribal character, and Bab Suleiman was able to control Qara Golan, which is currently Sulaymaniyah governorate, and took it as his center, and then the Papabani family began to expand at the expense of the neighboring emirates such as Sorani, Al-Bahdaniya, Rawndouziyah, Kafri, Harir, Qalja, Sarhak, Qara Dag and Idbel until its influence extended to Kirkuk, and in 1703, the emirate reached the peak of its strength when he took over its leadership in Bakr Bek, as he expanded the borders of The smaller, in addition to the mountainous section of the west side, and in 1704, the leaders of Hassan Bey, who is the governor of Baghdad, his army, and eliminated Bakr Bey and its right to the state of Shahrzor and Ain Khanh Bay as its ruler in 1721, which was characterized by the good relationship with the governors of Baghdad, which made the period of Khanah Bey a period full of prosperity and expansion, but this relationship did not last long. In 1726, the Babanese Kurds withdrew from the ranks of the Ottoman armies in a battle that took place between the Ottomans and the Afghans, and despite the return of Khanh Bey to the ranks of the Ottoman army and its participation in other wars, the governor of Baghdad did not forget that situation and managed the issue of killing him and that In 1728. After him, his brother Khaled Pasha was appointed, and the princes of the Babani family continued to dispute with the governors of Baghdad, relying on the Iranian force that was lurking on the eastern border.In 1788, Abdul Rahman Al-Babani took over the emirate of the Al-Baban, as the emirate during his reign reached the peak of its glory, and Abdul Rahman was distinguished by his political ambition and nationalism aspirations. He worked to establish an independent government in Iraq through his continuous clash with the Baghdad forces in several battles, the most important of which was the battle of (Jazb Kafri) in 1812, which ended with the defeat of Abdul Rahman Al-Babani. In addition, political independence was not the only goal for Abdul Rahman, but he coveted the Pashoism of Baghdad as well. Mahmoud Pasha took power after the death of Bad Rahman's mother in 1813, and thus with the support of Shahzadehzad Muhammad Ali Mirza, and thus Mahmoud Pasha became a danger After the rule of Daoud Pasha, who was appointed governor of Baghdad in 1813, so Dawood Pasha followed several ways to get rid of the rule of Mahmoud Pasha, including control of some important Kurdish areas and gaining the favor of some of the Babanid dynasty, and Mahmoud Pasha is considered the strongest and most famous mir of the Pabanid family because of his great ability and importance that made him able to withstand the governors of Baghdad on the one hand and the greedy Iranian force on the other hand, but Abdullah, who fled to Iran after a prior agreement between him and the Shahzadeh, who provided Abdullah with a tractor army in order to return and occupy Sulaymaniyah, and thus this was one of the reasons Which led to the weakness of natural capabilities in Sulaymaniyah and the inability of Baghdad's governors to stand up to Iranian forces led by Abdullah, which weakened the military aspect of the Habani family, which ended in 1850